(untitled) (Revista de Estudos da Linguagem, 2018)
Abstract: This work presents a pilot study for a prosodic analysis of two different spoken structures in spoken Italian within the theoretical framework of the Language into Act Theory (L-AcT): (i) chains of two or more Bound Comments (COB) that do not form a compositional informative and prosodic unit; (ii) compositional Information Units formed by two or more Multiple Comments (CMM), linked together by a conventional prosodic model that implements specific meta-illocutive structures. This work analyzes COBs and CMMs from the DB-IPIC Italian Minicorpus. Different prosodic cues are taken into account: f0 reset, pauses, final lengthening, intensity lowering and initial rush. The distinctive feature for COBs is a flat trend of f0 before the boundary, with a low number of f0 reset, while CMMs vary between different f0 shapes. Vowel elongation and a no rushing speech rate cooperate in perceiving the prolongation of one COB into another. Initial rush is a characteristic feature of CMMs, while the lengthening of the last vowel of the unit is easier to find at the end of a COB than in a CMM. Keywords: prosody; spontaneous speech segmentation; non-terminal breaks; L-AcT. Resumo: Este trabalho apresenta um estudo piloto sobre uma análise prosódica de duas estruturas distintas em italiano falado, sob a perspectiva da Teoria da Língua em Ato (L-AcT): (i) cadeiras de dois ou mais Comentários Ligados (COB) que não formam uma unidade informacional e prosódica composicional; (ii) unidades informacionais composicionais formadas por dois ou mais Comentários Múltiplos (CMM), ligados entre si por um modelo prosódico convencional que implementa estruturas metailocutivas específicas. Os COBs e CMMs analisados foram extraídos do minicorpus italiano disponível no DB-IPIC. Diferentes aspectos prosódicos são levados em conta: reset de f0, pausas, alongamento final, abaixamento de intensidade e rush inicial. O traço distintivo para os COBs é uma tendência a achatamento de f0 antes da fronteira, com um baixo número de reset de f0, enquanto os CMMs variam entre diferentes formatos de f0. Alongamento de vogal e uma velocidade de fala sem rushing cooperam na percepção do prolongamento de um COB naquele que o segue. O rush inicial é um traço característico dos CMMs, enquanto o alongamento da última vogal da unidade é mais fácil de encontrar ao final de um COB do que de um CMM. Palavras-chave: prosódia; segmentação da fala espontânea; quebras não-terminais; L-Act